Pengaruh Debt to Equity Ratio, Free Cash Flow, dan Pertumbuhan Perusahaan terhadap Kebijakan Dividen (Studi pada Perusahaan yang Terdaftar di BEI Periode 2019-2024) - Jonathan Andrian; Layyinaturrobaniyah Layyinaturrobaniyah (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study analyzes the determinants of dividend policy among 218 companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2024. Using the Dividend Payout Ratio (DPR) as a proxy, this research employs panel data regression with a Fixed Effect model and PCSE estimation to analyze 1,308 observations. The variables tested in this study include Free Cash Flow (FCF), corporate growth, and the Debt to Equity Ratio (DER). The results demonstrate that all three variables have a significant partial effect on the DPR. Specifically, Free Cash Flow has a positive and significant impact, indicating that the availability of excess cash encourages dividend distributions. Conversely, corporate growth and the Debt to Equity Ratio have a negative and significant influence, suggesting that expansion needs and debt obligations act as constraints on profit distribution. These findings emphasize that dividend decisions on the IDX are primarily determined by internal financial fundamentals, where companies prioritize the balance between liquidity, investment opportunities, and capital structure in determining their corporate strategies in Indonesia.